Sugarcane expansion in the microregion of Araraquara: a shift-share analysis - Dos Santos, Letícia Sarri [UNESP]; Lourenzani, Wagner Luiz [UNESP]; da Silva, Bruce Wellington Amorin [UNESP]; Miranda, Gustavo Arantes [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2024)
Sugarcane is one of the main crops in Brazilian agribusiness, covering a vast planted area that expands annually. Based on this, it is important to understand how the dynamics of this expansion occurred, to visualize whether there was the replacement of other crops or the incorporation of new areas. The objective of this research, therefore, was to analyze the sugarcane expansion by changes in land use. To this end, the shift-share method was applied, which, assuming a proportionality in the change in land use, allowed visualizing the main crops that incorporated and lost land, both in terms of planted area and new areas. Sugarcane was the main crop that incorporated land, but it was followed by soybeans, peanuts, and cassava. All other crops grown in the region lost land, including oranges, a traditional and important crop in the region. This may be due to more stability on returns of sugarcane and disease in the orange fields. There was also a reduction in the pastureland, which may be caused by competition with more intensive use of the land by some crops, such as sugarcane, and cheaper land in the northern region of the country. The results can contribute to the formulation of public and private policies regarding land use management.
Keywords: Araraquara; Land cover change; Shift-share; Sugarcane